Per un’educazione non antropocentrica : Elementi di post-umanesimo nell’arte di Eva Kot’átková - Fontana, Federica (Scenari, 2021)
The human being – meaning the unitary Cartesian subject qualitatively distinct from the natural and technological element – has been the exclusive reference for pedagogical reflection since its very inception. For centuries, pedagogy has been based on the recognition of an ontological discontinuity between man, animal, and machine. Moreover, this discontinuity has been the condition that made pedagogy itself possible the idea that the man is different from other biological species that made pedagogy possible and legitimated any educational practice aimed at the humanization and civilization of the man himself. In an age of profound technological, scientific and socio-cultural changes such as the present one, this model has revealed all its inadequacy and various researchers, both in Italy and abroad, are questioning how to extend educational practices beyond the anthroposphere, taking into account the relationship between human and non-human. The purpose of this article is to highlight the signs and perspectives of such crisis in the work of the Czech artist Eva Kot’átková challenging the anthropocentric paradigm and unveiling all its repressive forms. In her practice, she blends the cyborg suggestions of Dadaist photocollage with the Focaultian analysis of the institutions of control, and with a strong fascination for the infantile unconscious. While being shown as a place of alienation and constraint, human and animal bodies become a medium for new possible forms of nonverbal communication.